Magnitude do reforço como uma variável determinante da supressão condicionada da resposta humana de clicar - Silva, Ana Paula de Oliveira (2010)
The present study sought to investigate whether the magnitude of reinforcement is a relevant variable in determining the conditioned response suppression of "clicks", produced by presenting a negative punisher stimulus, in humans. Thirty participants were recruited and had tasked assemble puzzles 24 pieces on a computer. The responses observed was "click, drag, and engaging" pieces of the puzzle. Each side of piece placed in the correct position worth a point and, at the end of the experiment, the accumulated points were exchanged for cash. Participants were divided into 2 groups (A and B) in function maximum amount of cash received (R$10,00 or R$20,00 reais respectively). Subsequently, on the results obtained with the groups A and B, a new group was created with 6 participants who received R$10.00 reais and were exposed to ten presentations of conditioned aversive stimuli scheduled with a duration of 15 seconds each (groups A and B were exposed to only 3 presentations of this type, with duration of 1 minute each). Each participant, regardless of the group to which it belonged, performed the Test Task, and obtaining success, started the baseline. It was use the free operant procedure and the reinforcement schema FR1, both Baseline and Experimental Phase. The consequences for hits and errors also were the same. The pilot was initiated so that occurred the stabilization of response rate and the rate of reinforcements obtained. For participants of group a and group B, a schema VT or variable time entered into force at that stage, overlaid on the existing line FR1 schema: in three moments of the game the computer screen was green for 60 seconds and after that time, a fixed number of points (four points which is equivalent to around 10.5% of the total number of points that can be obtained on a puzzle) was withdrawn from the amount of points obtained so far. Loss was flagged by computer through a light sound (similar to coins falling on the floor). For the Group C conditions were identical, except the number of exhibits to the stimuli conditioned. None of the participants presented clearly a performance that could be considered response suppression. The performances were quite varied, and not consistent. The curves of the Experimental Phase present similar variations observed on the Baseline ones and are not consistent and exclusively quotas (and contiguous) upon presentation of the green screen